2014
DOI: 10.1176/appi.ps.201200572
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Peer-Run Antistigma Photovoice Intervention

Abstract: The photovoice intervention demonstrated promise for reducing self-stigma and enhancing proactive coping with prejudice and discrimination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
148
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(150 citation statements)
references
References 14 publications
1
148
0
1
Order By: Relevance
“…Future studies should seek to establish associations between stigma resistance and depression-related outcomes. Previous research20 has indicated that PhotoVoice itself may be associated with lowering of stigma. Therefore, it is possible that participation in this study is partly or entirely responsible for the prominence of self-stigma resistance found.…”
Section: Discussionmentioning
confidence: 95%
“…Future studies should seek to establish associations between stigma resistance and depression-related outcomes. Previous research20 has indicated that PhotoVoice itself may be associated with lowering of stigma. Therefore, it is possible that participation in this study is partly or entirely responsible for the prominence of self-stigma resistance found.…”
Section: Discussionmentioning
confidence: 95%
“…There is some preliminary evidence to suggest that interventions incorporating storytelling are helpful in reducing symptoms and increasing functioning (Gunnarsson and Eklund, 2009;Roe et al, 2014;Russinova et al, 2014). However, the lack of qualitative literature exploring the individual's experience of these interventions means that attempts to capture outcomes are being made without clarity around which domains to measure.…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of the environment will reflect dietary practices and food access, which may inform environmental cues within the home [8,9,10]. Additionally, reflecting on insights to one's environment gained through photo-texting may provide an impetus for change [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These methods have been used both in combination with large research team HFE assessments and with self-assessment as a sole indicator of the HFE. The strengths of the self-assessment components were increased self-empowerment and reduced self-stigmatization, which led to increased nutritional knowledge and perceived responsibility [11,12,14]. Through the self-awareness gained from self-assessment, barriers to an improved HFE can be identified, as can facilitators, and this can lead to potentially beneficial goal setting and an increase in healthy behaviors [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%